Fungsi Dan Keistimewaan Makna Candi Prambanan Bagi Umat Hindu Di Indonesia - Ni Putu Ratni (Jurnal Penelitian Agama Hindu, 2020)
This research is a qualitative research that examines the divine meaning of the Prambanan Temple for Hindus in Indonesia. This research was conducted at the Prambanan Temple Complex, Central Java, the National Museum of Indonesia, the Jakarta National Library, and the Yogyakarta Archaeological Agency. Data analysis was performed using qualitative analysis known as Ethnographic Content Analysis (ECA), a combination of objective content analysis with participant observation. Prambanan is a Hindu temple complex built using the Vāstupuruṣamaṇḍala concept, a development concept carefully designed to present Devata as the center of the mandala on earth. The construction of the Prambanan temple uses the calculation of Vāstu Śāstra-Śilpa Śāstra, starting with careful selection of the place, carrying out the preliminary ceremonies before construction to development, and setting up statues in the temple. Previous researchers concluded that Prambanan was built during the golden age of the Sailendra dynasty, which lasted for 110 years (750 - 860 AD). The construction involved several Brahmins, Śilpins, and various other skills and took a long time. The original name of the Prambanan Temple is Śivagrha which means the House of Śiva or Śivalaya-realm Śiva is also Lord iva's stana. Śivagrha is a temple complex worshiping the Tri Murti of Brahma, Visnu, and Śiva, as Creator, Preserver, and Consolidator. However, from the building's structure and the search for the text, this temple has a Śivaistic concept, that is, Śiva is worshiped as the supreme Devata. However, it also attracts other devotees and unites them, with the construction of other devatas worshiped in the various temples in the complex. Thus, Prambanan became a center of Hindu worship, a center of study, a center for Brahmin activity, a spiritual center, and a yatra destination. Prambanan is a Hindu Masterpiece, is useful in the past, but after twelve centuries, it continues to provide benefits to the surrounding community, local government, and state. This beautiful temple should continue to be cared for and sanctified as a very magnificent temple in Indonesia.